Erfahrungen von HausärztInnen mit COVID-19 und der Pandemie – ein Survey nach der ersten Pandemiewelle im März/April 2020 - Schrader, Hanna; Borgulya, Gábor; Parisi, Sandra; Joos, Stefanie; Kaduszkiewicz, Hanna; Barzel, Anne; Raus, Christina; Sanftenberg, Linda; Kühlein, Thomas; Maun, Andy; Schmidt, Julia; Linde, Klaus; et al. (Gesundheitswesen, 2023)
Background and Objectives The first wave of the COVID-19 pandemic (Mar-Apr 2020) posed significant challenges for primary care. The goal of this study was to analyse the burden of the crisis situation as experienced by the general practitioners (GPs) at its beginning and over the course of the pandemic and to identify factors predictive of the sense of being overburdened. Methods In this cross-sectional study, a total of 6300 randomly selected GPs in four federal states of Germany were contacted per post in order to survey changes in health care they provided and their psychological burden in the context of the pandemic between August and October 2020. Results The response rate was 23%; 46% of the participants were female. At the beginning of the pandemic, 40 % of the participants experienced a high or a very high level of being overburdened; later on, it was only 10%. With increasing numbers of COVID patients, the sense of being overburdened increased, as also their perceived capability to care for COVID patients. Predictors of a sense of being overburdened were, among others, a high level of psychological stress, excessive organising efforts, poor capability to care for COVID patients, and scarce supply of protective equipment. Conclusion Despite a sense of being overburdened initially, GPs felt increasingly capable of caring for COVID patients. To help GPs in future crisis situations like this pandemic, organization of care should be simplified to the extent possible so that they can focus on patient care.
CRIS-Team Scopus Importer:2023-07-07
Keywords: COVID-19; Hausärztliche Versorgung; Pandemiebewältigung; Überforderungsgefü